2019
DOI: 10.3920/bm2018.0149
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Bacillus subtilis KATMIRA1933 and Bacillus amyloliquefaciens B-1895 on the productivity, reproductive aging, and physiological characteristics of hens and roosters

Abstract: The study aims at investigating the effect of preparations of two bacilli strains on laying hens and roosters. Preparations were based on the strains Bacillus subtilis KATMIRA1933 and Bacillus amyloliquefaciens B-1895. Several groups of roosters and hens received a preparation based on either strain, or a mixture of both, from the first day to the last day of poultry in production. These preparations improved egg production, quality of sperm production, quality/hatchery of eggs, and slowed down the reproductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…It is important to note that dietary Pal-Pro has a positive effect on fertilisation rate, embryo mortality, hatchability of fertile eggs, and health hatched chocks rate. Prazdnova et al (2019) demonstrated that Bacillus subtilis increased fertilisation rate and reduced the number of embryo deaths during the first 7 days of incubation. And Mazanko et al (2018) also reported that bacillus probiotic positively affected the hatchability of laying hens and sperm production of roosters.…”
Section: Discussionmentioning
confidence: 98%
“…It is important to note that dietary Pal-Pro has a positive effect on fertilisation rate, embryo mortality, hatchability of fertile eggs, and health hatched chocks rate. Prazdnova et al (2019) demonstrated that Bacillus subtilis increased fertilisation rate and reduced the number of embryo deaths during the first 7 days of incubation. And Mazanko et al (2018) also reported that bacillus probiotic positively affected the hatchability of laying hens and sperm production of roosters.…”
Section: Discussionmentioning
confidence: 98%
“…B. licheniformis can alleviate heat stress-induced impairments of egg production [ 28 ]. Probiotic B. subtilis can increase laying performance via several mechanisms [ 29 , 30 , 31 ]. Besides Bacillus and Lactobacillus , many other bacteria are used in the poultry industry as probiotics, such as Clostridium butyricum , which can counteract the diverse stresses in the body and has the ability to improve laying hens’ performance and egg quality [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are many facts that spores of Bacillus spp. In the diet have positive effects on reproductive functions [ 49 , 50 , 51 ]. This allows us to assume that the decrease in reproductive functions in animals of different genotypes on the autoclaved diet is associated with inactivation of Bacillus spp.…”
Section: Discussionmentioning
confidence: 99%